The last widow - Slaughter, Karin, 1971- (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2019)
On a hot summer night, a scientist from the Centers for Disease Control is grabbed by unknown assailants in a shopping center parking lot. One month later, the serenity of a sunny Sunday afternoon is shattered by the boom of a ground-shaking blast. Medical examiner Sara Linton and her partner Will Trent, an investigator with the Georgia Bureau of Investigation, rush to the scene. When the assailants abduct Sara, Will goes undercover to save her and prevent a massacre--putting his own life on the line for the woman and the country he loves.
A novel.
Keywords: Trent, Will -- (Fictitious character) -- Fiction; Linton, Sara -- (Fictitious character) -- Fiction; Government investigators -- Georgia -- Atlanta -- Fiction; Medical examiners (Law) -- Georgia -- Atlanta -- Fiction; Undercover operations -- Fiction; Disappeared persons -- Fiction; Bombings -- Fiction; Atlanta (Ga.) -- Fiction; Georgia -- Fiction; Thrillers (Fiction); Detective and mystery fiction